FACTORS INFLUENCING CUSTOMER SATISFACTION IN THE AIRLINE INDUSTRY: THE CASE OF M AIRWAYS - Tangthaweetham, Thidarat; Praditbatuga, Piyathida; TREETIPBUT, Santhiti (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research is aimed to determine whether service quality, in terms of airline tangibles, terminal tangibles, personnel, empathy, and image, influences customer satisfaction towards M Airways. Sample of this study was first, and business passengers of M Airways. The study employed the questionnaire method as a tool to collect data from 100 respondents. The Multiple Linear Regression (MLR) analysis of image, terminal tangibles, airline tangibles, empathy, and personnel have proven to be statistically significant in influencing customer satisfaction [r2 = .502, Adjust r2 = 0.476, F = 18.978, p = .000]. Moreover, image had the strongest influence on customer satisfaction, followed by terminal tangibles, airline tangibles, empathy, and personnel, respectively. Therefore, if M Airways would like to increase its level of customer satisfaction, it has to focus most on improving the level of positive perception on the airline image, followed by terminal tangibles, airline tangibles, empathy, and personnel, respectively.